An organic-inorganic hybrid method for synthesizing bifunctional fluorine-doped armor-type nanomaterials, preparation method and application
The synthesis of bifunctional fluorine-doped armor-type nanomaterial NiO1-xFx/Ni@C/NF through the organic-inorganic hybrid method solves the problem of high energy consumption and poor stability of nickel-based catalysts, achieving low-energy consumption, efficient and stable urea degradation catalytic performance, avoiding the generation of dangerous exhaust gas, and improving the stability of the catalyst and the exposure of active sites.
Patent Information
- Application Number
- CN202211248001.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-12
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-10-12
AI Technical Summary
The prior art When electrochemical oxidation treatment of urea wastewater, the nickel-based catalyst has high energy consumption and poor stability. Traditional fluorine doping methods are prone to produce dangerous exhaust gases, and NiO nanoparticles are prone to agglomeration, which limits their application.
The bifunctional fluorine-doped armor-type nanomaterial NiO1-xFx/Ni@C/NF was synthesized by the organic-inorganic hybrid method, and the fluorine-containing organic matter was interposed between the Ni(OH)2 layers by hydrothermal method, and NiO1-xFx nanoparticles and carbon layer clad structure was formed by annealing, avoiding the defects of the traditional method.
It achieves low-energy consumption, efficient and stable urea degradation catalytic performance, avoids the generation of dangerous exhaust gas, improves the stability of the catalyst and the exposure of active sites, and improves the efficiency of electrocatalytic urea oxidation and hydrogen precipitation.
Smart Images

Figure CN115679363B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of materials and electrochemical energy storage new energy technology, and in particular to an electrocatalytic urea degradation catalyst, specifically an organic-inorganic hybrid synthesis of bifunctional fluorine-doped armor-type nanomaterials, a preparation method and application thereof. Background Art
[0002] Urea (CO(NH2)2) is widely present in industrial wastewater and domestic sewage. In recent years, urea-rich wastewater has become the main source of water pollution due to eutrophication. When urea wastewater that does not meet the treatment standards is discharged into the water body, it is easy to cause eutrophication of the water body. In addition to the odor of drinking water, it will also cause the death of fish, shrimp and other organisms in the water, and even the drying up of lakes. Urea can be converted into nitrates and toxic ammonia, posing a threat to human health. Therefore, electrochemical oxidation treatment of urea in wastewater, converting urea into harmless N2 and CO2, has received great attention from the research community. Electrochemical oxidation treatment of urea wastewater involves two reactions: hydrogen evolution (HER) at the cathode end and urea oxidation (UOR) at the anode end. In order to reduce the cost of industrial preparation and the complexity of the process flow, it is imperative to develop HER and UOR bifunctional catalysts.
[0003] Limited by the complex six-electron transfer process and multiple intermediate adsorption / desorption steps, the kinetics of UOR is usually inherently slow. Therefore, the main energy consumption of electro-oxidative degradation of urea comes from the UOR end. It has been recognized that among various materials including precious metal-based compounds, nickel (Ni)-based catalysts have higher oxidation current density for UOR in alkaline media. However, this type of material usually has disadvantages such as high overpotential and slow kinetics, which limits its further development and application. In order to further improve the intrinsic activity and stability of nickel-based catalysts, the strategy of constructing heterojunctions or doping heteroatoms is adopted to produce more interfaces, expose more active sites, induce atomic distortion or internal defects to adjust the electronic structure. Among them, the F element is believed to be able to effectively adjust the electronic structure of Ni-based catalysts due to its highest electronegativity, thereby adjusting the adsorption strength of the catalyst on the matrix or intermediates, and ultimately improving its electrochemical performance. However, most of the traditional fluorine doping strategies use ammonium fluoride as the fluorine source for annealing. This method produces a large amount of HF tail gas, which poses a threat to the environment and human health. In addition, during the electrochemical process, Ni of nickel-based catalysts is easily precipitated, resulting in a large loss of active sites.
[0004] Therefore, how to provide a method that has low energy consumption, is suitable for safe production and can prepare an efficient and stable urea degradation catalyst is a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention
[0005] To this end, the technical problem to be solved by the present invention is to provide an organic-inorganic hybrid method for synthesizing bifunctional fluorine-doped armor-type nanomaterials with low energy consumption and suitable for safe production, as well as a preparation method and application.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] An organic-inorganic hybrid method for synthesizing bifunctional fluorine-doped armor-type nanomaterials, composed of NiO 1-x F x / Ni and carbon layer composition, NiO 1-x F x / Ni@C is directly grown on nickel foam (NF) to obtain NiO 1-x F x / Ni@C / NF nanomaterials, where 0 <x<1。
[0008] The above organic-inorganic hybrid method synthesizes bifunctional fluorine-doped armor-type nanomaterials, using NiO 1-x F x / Ni is the core, and the carbon layer is the "armor".
[0009] The carbon layer acts as a "armor" to improve the conductivity of the catalyst while preventing the catalyst from being corroded. 1-x F x / Ni@C is directly grown on nickel foam (NF), which avoids the binder from covering the active sites and effectively prevents the powder from falling off the nickel foam NF skeleton.
[0010] The above-mentioned method for preparing bifunctional fluorine-doped armor-type nanomaterials by organic-inorganic hybrid method comprises the following steps:
[0011] (1) adding a metal nickel salt and a fluorine-containing organic compound into a solvent and stirring until dissolved to obtain an initial mixed solution;
[0012] (2) transferring the initial mixed solution to a polytetrafluoroethylene reactor, adding nickel foam, performing a hydrothermal reaction, and obtaining a reaction product by centrifugation;
[0013] (3) washing the reaction product with ethanol and vacuum drying to obtain a Ni(OH)2 precursor of a fluorine-containing organic intercalation layer supported by nickel foam NF, i.e., Ni(OH)2-F / NF;
[0014] (4) placing the precursor in a tube furnace for annealing to obtain a bifunctional fluorine-doped armor-type nanomaterial, namely NiO 1-x F x / Ni@C / NF nanomaterials.
[0015] The synthesis method of the present invention is to use the first step of hydrothermal method to allow fluorine-containing organic matter to intercalate into the Ni(OH)2 interlayer, and at the same time serve as a carbon source and a fluorine source. The synthesized precursor Ni(OH)2-F / NF has a three-dimensional skeleton-loaded nanosheet array structure. Then, after the second step of annealing, Ni(OH)2 and fluorine-containing organic matter are thermally decomposed. During the decomposition process, Ni(OH)2 is dehydrated to form NiO; the CF bond of the fluorine-containing organic matter is broken, and the free F atoms enter the NiO lattice to form NiO 1-x F x Nanoparticles; the remaining organic matter forms a nanocarbon layer that wraps NiO 1-x F x Nanoparticles form an armor layer. During the encapsulation process, some of the carbon in the carbon layer is mixed with NiO 1-x F x Oxidation-reduction reaction occurs, making NiO 1-x F x Partially reduced to form NiO 1-x F x / Ni, eventually forming NiO 1-x F x / Ni@C / NF multi-layered armor-type nanomaterials. The multi-layered structure is conducive to the mutual transfer of electrons at the interface, thereby adjusting the electronic structure of the active site, optimizing its adsorption strength to the reaction intermediates, and improving the reaction kinetics rate.
[0016] The above-mentioned method for preparing bifunctional fluorine-doped armor-type nanomaterials by organic-inorganic hybrid method, in step (1), the metal nickel salt is one of Ni(NO3)2·6H2O, NiSO4, NiCl2 or NiBr2; the fluorine-containing organic compound is one of 4-fluorosalicylic acid, 2,4-difluorobenzoic acid, 3-fluoroacetic acid, 4-fluorophenylacetic acid; and the solvent is a three-phase mixed solution of N,N-dimethylformamide (DMF), water and ethanol.
[0017] At present, pure water is the most commonly used solvent for preparing organic intercalated Ni(OH)2 materials. In the present patent application, the preparation solvent is a three-phase mixed solution of DMF, water and ethanol, so the nanosheets of the final product are thinner, which effectively prevents the aggregation of nanoparticles in the next reaction process and is conducive to exposing more active sites, thereby improving its catalytic performance.
[0018] In the above-mentioned method for preparing a bifunctional fluorine-doped armor-type nanomaterial by an organic-inorganic hybrid method, the molar ratio of the nickel element of the metal nickel salt to the fluorine element of the fluorine-containing organic matter is (0.1-1): (0.1-4), and the volume ratio of N,N-dimethylformamide (DMF), water, and ethanol in the solvent is V DMF :V 水 :V 乙醇=(4~2): (3~1.5):(1~0.5).
[0019] The molar ratio of metal nickel salt and fluorine-containing organic matter is one of the main reasons affecting the morphology of the precursor.
[0020] When the molar ratio of the metal nickel salt to the fluorine-containing organic matter is 1:0.5 and 1:1, Ni(OH)2-F is a nanosheet structure, and when the molar ratio of the metal nickel salt to the fluorine-containing organic matter is 1:2 and 1:4, Ni(OH)2-F is a nanorod structure. When the molar ratio of the metal nickel source to the fluorine-containing organic matter is less than or equal to 1:1, the synthesized precursor is a nanosheet structure, and when the ratio is greater than 1:1, the synthesized precursor is a nanorod structure.
[0021] Compared with the nanorod structure, the two-dimensional nanosheet structure is more conducive to exposing more active sites and improving the catalytic efficiency of the catalyst.
[0022] In the above-mentioned method for preparing bifunctional fluorine-doped armor-type nanomaterials by an organic-inorganic hybrid method, in step (2), the hydrothermal reaction temperature is 120° C. to 160° C., and the reaction time is 6 to 12 hours;
[0023] In step (3), the vacuum drying temperature is 40-60° C. and the drying time is 8 h. The drying temperature cannot be too high, otherwise the sample will be destroyed.
[0024] In step (4), during the annealing treatment in the tube furnace, the reaction temperature is 400-600°C and the reaction time is 30 minutes. If the reaction temperature is too low, the organic matter cannot be decomposed to form a carbon layer; if the temperature is too high, NiO 1-x F x / Ni nanoparticles aggregate rapidly, hindering the exposure of active sites.
[0025] An application of an organic-inorganic hybrid method to synthesize a bifunctional fluorine-doped armor-type nanomaterial, wherein the bifunctional fluorine-doped armor-type nanomaterial NiO 1-x F x / Ni@C / NF is used as an electrocatalyst in an electrocatalytic hydrogen evolution device; in the electrocatalytic hydrogen evolution device, the working electrode is NiO 1-x F x / Ni@C / NF nanomaterial, the reference electrode is a Hg / HgO electrode, the counter electrode is a carbon rod, and the electrolyte is a KOH solution; the size of the electrode sheet is 1-4 cm×1-4 cm.
[0026] An application of an organic-inorganic hybrid method to synthesize a bifunctional fluorine-doped armor-type nanomaterial, wherein the bifunctional fluorine-doped armor-type nanomaterial NiO 1-x F x / Ni@C / NF is used as an electrocatalyst in an electrocatalytic urea oxidation device. In the electrocatalytic urea oxidation device, the working electrode is NiO 1-x F x / Ni@C / NF nanomaterial, the reference electrode is a Hg / HgO electrode, the counter electrode is a carbon rod, the electrolyte is a KOH solution containing urea, and the electrolyte is 1 mol / L potassium hydroxide + 0.33 mol / L urea solution; the size of the electrode sheet is 1-4 cm×1-4 cm.
[0027] An application of an organic-inorganic hybrid method to synthesize a bifunctional fluorine-doped armor-type nanomaterial, wherein the bifunctional fluorine-doped armor-type nanomaterial NiO 1-x F x / Ni@C / NF for electrocatalytic urea degradation.
[0028] The above-mentioned organic-inorganic hybrid method is used to synthesize bifunctional fluorine-doped armor-type nanomaterials. In the electrocatalytic degradation of urea, the anode electrode sheet and the cathode electrode sheet are both NiO 1-x F x / Ni@C / NF nanomaterial, the electrolyte is a KOH solution containing urea, 1 mol / L potassium hydroxide + 0.33 mol / L urea solution, and the size of the anode electrode sheet and the cathode electrode sheet are both 1~4cm×1~4cm.
[0029] The electrocatalytic urea degradation device is low-cost, simple to operate, and has superior performance. It can achieve urea degradation under alkaline conditions and has broad application prospects in urea wastewater resource utilization, energy conversion and storage, etc.
[0030] The technical solution of the present invention achieves the following beneficial technical effects:
[0031] 1. The present invention uses fluorine-containing organic matter as both a carbon source and a fluorine source, anchored in the Ni(OH)2 interlayer by intercalation, and undergoes a one-step annealing process to simultaneously achieve fluorine doping in the NiO lattice and outer coating of the carbon layer, ultimately forming a dual-functional fluorine-doped armor-type nanomaterial, namely NiO 1-x F x / Ni@C / NF. The present invention overcomes the disadvantages of the traditional fluorine doping method that dangerous tail gas is easily generated and NiO nanoparticles are easily agglomerated, and is simple, safe and pollution-free.
[0032] 2. NiO prepared by the present invention 1-x F x / Ni@C / NF drives 10 mA cm in electrocatalytic hydrogen evolution device -2The current density only needs 42mV overpotential, which is comparable to commercial Pt / C. The present invention uses transition metal as metal source, which is low in price and abundant in output, and solves the problem of high price and scarce resources of traditional electrocatalytic hydrogen evolution catalysts.
[0033] 3. NiO prepared by the present invention 1-x F x In the electrocatalytic urea oxidation device, / Ni@C / NF only needs 1.31, 1.34, and 1.36 V to drive 10, 50, and 100 mA cm -2 At 10 mA cm -2 The invention solves the problems of high energy consumption and poor stability of conventional electrocatalytic urea oxidation catalysts.
[0034] 4. Bifunctional fluorine-doped armor-type nanomaterial NiO prepared by the method of the present invention 1-x F x / Ni@C / NF can not only be used as a dual-functional catalyst for HER and UOR, but also can efficiently degrade urea wastewater into N2 and CO2. 1-x F x / Ni@C / NF acts as both cathode and anode, and the degradation rate of urea wastewater with a urea concentration of 0.33M can reach 94.86%, which can meet the requirements of urea wastewater treatment in multiple occasions such as industry and life, and realize wastewater resource utilization. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a reaction preparation principle diagram of the organic-inorganic hybrid method for synthesizing bifunctional fluorine-doped armor-type nanomaterials disclosed in the present invention;
[0036] Figure 2a This is the SEM image of the precursor material Ni(OH)2-FSA / NF prepared in this example;
[0037] Figure 2b XRD pattern of the precursor material Ni(OH)2-FSA / NF prepared in this example;
[0038] Figure 3a The bifunctional fluorine-doped armor-type nanomaterial NiO prepared in this example 1-x F x SEM image of / Ni@C / NF;
[0039] Figure 3b The bifunctional fluorine-doped armor-type nanomaterial NiO prepared in this example 1-x F x TEM image of / Ni@C / NF;
[0040] Figure 4a The bifunctional fluorine-doped armor-type nanomaterial NiO prepared in this example 1-x F x XRD pattern of / Ni@C / NF;
[0041] Figure 4b The bifunctional fluorine-doped armor-type nanomaterial NiO prepared in this example 1-x F x Raman spectrum of / Ni@C / NF;
[0042] Figure 5 The bifunctional fluorine-doped armor-type nanomaterial NiO prepared in this example 1-x F x Electrocatalytic performance diagram of / Ni@C / NF as HER catalyst (LSV diagram of compound HER);
[0043] Figure 6a The bifunctional fluorine-doped armor-type nanomaterial NiO prepared in this example 1-x F x Electrocatalytic performance diagram of / Ni@C / NF as UOR catalyst (LSV diagram of compound UOR);
[0044] Figure 6b The bifunctional fluorine-doped armor-type nanomaterial NiO prepared in this example 1-x F x Electrocatalytic stability diagram of / Ni@C / NF as UOR catalyst (chronopotentiometry diagram of compound UOR);
[0045] Figure 7a The bifunctional fluorine-doped armor-type nanomaterial NiO prepared in this example 1-x F x Electrocatalytic performance diagram of / Ni@C / NF as urea degradation catalyst (absorbance diagram);
[0046] Figure 7b The bifunctional fluorine-doped armor-type nanomaterial NiO prepared in this example 1-x F x Performance comparison of urea degradation rate between / Ni@C / NF and undoped fluorine control sample. DETAILED DESCRIPTION
[0047] Example
[0048] 1. Preparation of an asymmetrically coordinated dual-site metal organic framework nanomaterial, specifically comprising the following steps:
[0049] (1) 1 mmol Ni(NO3)2·6(H2O) and 1 mmol 4-fluorosalicylic acid were added to a DMF / water / ethanol three-phase mixed solvent (V DMF :V 水 :V 乙醇 =4:3:1), stirring until dissolved to obtain an initial mixed solution;
[0050] (2) transferring the initial mixed solution to a polytetrafluoroethylene reactor, adding nickel foam of 2×4 cm in size, reacting at 120° C. for 12 hours, and centrifuging to obtain a reaction product;
[0051] (3) washing the reaction product with alcohol and vacuum drying at a temperature of 60° C. for 8 h to obtain a NF-supported 4-fluorosalicylic acid intercalated Ni(OH)2 precursor, namely Ni(OH)2-FSA / NF.
[0052] (4) placing the above precursor in a tube furnace, heating it to 450°C at a rate of 5°C / min, and keeping it at 450°C for 30 minutes. When the furnace temperature drops to room temperature, the bifunctional fluorine-doped armor-type nanomaterial, i.e., NiO 1-x F x / Ni@C / NF armor-type nanomaterials.
[0053] In this example, carbon-coated NiO was synthesized using an organic-inorganic hybrid method. 1-x F x / Ni nanomaterials provide a reference for the synthesis of fluorine-doped armor-type nanomaterials; the synthesized materials have HER and UOR dual functional properties; their application in urea oxidation can be extended to urea wastewater degradation.
[0054] 2. Characterization of bifunctional fluorine-doped armor-type nanomaterials
[0055] Figure 1 This is a simple schematic diagram of one-step hydrothermal synthesis. The morphology of the precursor can be adjusted by controlling the ratio of the metal nickel source and the fluorine-containing organic compound. When the molar ratio of the metal nickel source to the fluorine-containing organic compound is less than or equal to 1:1, the synthesized precursor is a nanosheet structure, and when the ratio is greater than 1:1, the synthesized precursor is a nanorod structure. Compared with the nanorod structure, the two-dimensional nanosheet structure is more conducive to exposing more active sites and improving the catalytic efficiency of the catalyst.
[0056] Figure 2a and 2b The SEM and XRD patterns of the precursor material Ni(OH)2-FSA / NF prepared in this example. Figure 2a It can be seen that the obtained Ni(OH)2-FSA / NF precursor is a nanosheet array structure. Figure 2bXRD shows that the Ni(OH)2-FSA / NF synthesized in this example is a typical organic intercalated Ni(OH)2 structure. Compared with the conventional salicylic acid intercalated Ni(OH)2, its (003) peak shifts to the left, proving the introduction of F atoms.
[0057] Figure 3a and 3b The SEM and TEM images of the dual-functional fluorine-doped armor-type nanomaterial prepared in this embodiment are shown in FIG. Figure 3a It can be seen that the bifunctional fluorine-doped armor-type nanomaterial prepared in this embodiment is a nanosheet structure. Figure 3b It can be seen that the nanosheet is composed of extremely small nanoparticles and carbon layers.
[0058] Figure 4a and 4b The XRD and Raman spectra of the bifunctional fluorine-doped armor-type nanomaterial prepared in this embodiment are shown in Figure 1. It can be seen that the main components of the bifunctional fluorine-doped armor-type nanomaterial prepared in this embodiment are Ni, NiO 1-x F x and carbon.
[0059] Example 2: The bifunctional fluorine-doped armor-type nanomaterial was used as an electrocatalyst for an electrocatalytic hydrogen evolution device, and the HER catalytic activity of the prepared catalyst was tested using a three-electrode system.
[0060] The bifunctional fluorine-doped armor-type nanomaterial (1 cm×1 cm) prepared in Example 1 was used as the working electrode, the graphite carbon rod was used as the auxiliary electrode, the Hg / HgO electrode was used as the reference electrode, 100 mL of 1 M KOH was prepared as the electrolyte, and its HER catalytic activity was tested.
[0061] from Figure 5 It can be seen that the bifunctional fluorine-doped armor-type nanomaterial prepared in the embodiment is a HER catalyst, and the system drives 10 mA cm -2 The overpotential of the current density is 42 mV, which is much lower than that of the undoped F-NiO / Ni@C / NF sample (205 mV). Figure 5 As shown in Figure 6, nickel foam (NF): 1x1 cm, purchased from Cybermaterials.com; platinum carbon (Pt / C): McLean; NiO / Ni@C / NF sample was used as a comparative sample and was prepared by using the preparation method of Example 1 except that 4-fluorosalicylic acid was replaced by salicylic acid.
[0062] Example 3: The bifunctional fluorine-doped armor-type nanomaterial was used as an electrocatalyst in an electrocatalytic urea oxidation device, and the UOR catalytic activity of the prepared catalyst was tested using a three-electrode system.
[0063] The bifunctional fluorine-doped armor-type nanomaterial (1 cm×1 cm) prepared in Example 1 was used as the working electrode, the graphite carbon rod was used as the auxiliary electrode, the Hg / HgO electrode was used as the reference electrode, and 1 M KOH+0.33 M urea was prepared as the electrolyte to test its UOR catalytic activity.
[0064] from Figure 6a It can be seen that the bifunctional fluorine-doped armor-type nanomaterial prepared in Example 1 is used as a UOR catalyst, and only 1.31, 1.34, and 1.36 V are required to drive 10, 50, and 100 mA cm, respectively. -2 of current density. Figure 6a Ruthenium dioxide (RuO2) was purchased from MacLean. Figure 6b It can be seen that the bifunctional fluorine-doped armor-type nanomaterial prepared in the embodiment can be used as a UOR catalyst at 10 mA cm -2 It can run stably for 50h at a current density of .
[0065] Example 4: Dual-functional fluorine-doped armor-type nanomaterial NiO 1-x F x / Ni@C / NF was used for electrocatalytic urea degradation, and the urea degradation efficiency of the prepared catalyst was tested by a two-electrode system.
[0066] The urea degradation was tested by bipolar electrical degradation, and both the cathode and cathode were bifunctional fluorine-doped armor-type nanomaterials (4 cm×4 cm) prepared in the example.
[0067] from Figure 7a and Figure 7b It can be seen that the bifunctional fluorine-doped armor-type nanomaterial prepared in Example 1 is used as a catalyst for urea degradation, and its degradation rate of urea can reach 94.86%, which is much higher than the NiO / Ni@C / NF sample (23.60%) without F doping. After three cycles, the urea degradation rate can still reach 88.30%, indicating that the bifunctional fluorine-doped armor-type nanomaterial has good degradation performance for urea, and the degradation performance is stable.
[0068] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the claims of this patent application.
Claims
1. An organic-inorganic hybrid method for synthesizing bifunctional fluorine-doped armor-type nanomaterials, characterized in that: NiO 1-x F x / Ni and carbon layer composition, NiO 1-x F x / Ni@C is directly grown on nickel foam (NF) to obtain NiO 1-x F x / Ni@C / NF nanomaterials, where 0 <x<1; Among them, the preparation method of the bifunctional fluorine-doped armor-type nanomaterial synthesized by organic-inorganic hybrid method includes the following steps: (1) adding metal nickel salt and fluorine-containing organic matter into a solvent and stirring until dissolved to obtain an initial mixed solution; (2) transferring the initial mixed solution to a polytetrafluoroethylene reactor, adding nickel foam, performing a hydrothermal reaction, and obtaining a reaction product by centrifugation; (3) washing the reaction product with ethanol and vacuum drying to obtain a Ni(OH)2 precursor of a fluorine-containing organic intercalation layer supported by nickel foam NF, namely Ni(OH)2-F / NF; (4) placing the precursor in a tube furnace for annealing to obtain a bifunctional fluorine-doped armor-type nanomaterial, namely NiO 1-x F x / Ni@C / NF nanomaterials.
2. The method for synthesizing bifunctional fluorine-doped armor-type nanomaterials by an organic-inorganic hybrid method according to claim 1, characterized in that: NiO 1-x F x / Ni is the core and the carbon layer is the "armor".
3. A method for preparing a bifunctional fluorine-doped armor-type nanomaterial by an organic-inorganic hybrid method according to any one of claims 1-2, characterized in that: The steps include: (1) adding metal nickel salt and fluorine-containing organic matter into a solvent and stirring until dissolved to obtain an initial mixed solution; (2) transferring the initial mixed solution to a polytetrafluoroethylene reactor, adding nickel foam, performing a hydrothermal reaction, and obtaining a reaction product by centrifugation; (3) washing the reaction product with ethanol and vacuum drying to obtain a Ni(OH)2 precursor of a fluorine-containing organic intercalation layer supported by nickel foam NF, i.e., Ni(OH)2-F / NF; (4) placing the precursor in a tube furnace for annealing to obtain a bifunctional fluorine-doped armor-type nanomaterial, namely NiO 1-x F x / Ni@C / NF nanomaterials.
4. The method for preparing a bifunctional fluorine-doped armor-type nanomaterial synthesized by an organic-inorganic hybrid method according to claim 3, characterized in that: In step (1), the metal nickel salt is one of Ni(NO3)2∙6H2O, NiSO4, NiCl2 or NiBr2; the fluorine-containing organic compound is one of 4-fluorosalicylic acid, 2,4-difluorobenzoic acid, 3-fluoroacetic acid, and 4-fluorophenylacetic acid; and the solvent is a three-phase mixed solution of N,N-dimethylformamide (DMF), water, and ethanol.
5. The method for preparing a bifunctional fluorine-doped armor-type nanomaterial synthesized by an organic-inorganic hybrid method according to claim 3, characterized in that: The molar ratio of nickel element in the metal nickel salt to fluorine element in the fluorine-containing organic matter is (0.1~1):(0.1~4), and the volume ratio of N,N-dimethylformamide (DMF), water and ethanol in the solvent is V DMF : V 水 : V 乙醇 =(4~2): (3~1.5): (1~0.5).
6. The method for preparing a bifunctional fluorine-doped armor-type nanomaterial synthesized by an organic-inorganic hybrid method according to claim 3, characterized in that: In step (2), the hydrothermal reaction temperature is 120°C to 160°C, and the reaction time is 6 to 12 h; In step (3), the vacuum drying temperature is 40-60°C and the drying time is 8 h; In step (4), during the annealing treatment in the tubular furnace, the reaction temperature is 400-600°C and the reaction time is 30 min.
7. An application of an organic-inorganic hybrid method to synthesize bifunctional fluorine-doped armor-type nanomaterials, characterized in that: The bifunctional fluorine-doped armor-type nanomaterial NiO according to any one of claims 1 to 6 1-x F x / Ni@C / NF is used as an electrocatalyst in an electrocatalytic hydrogen evolution device; in the electrocatalytic hydrogen evolution device, the working electrode is NiO 1-x F x / Ni@C / NF nanomaterial, the reference electrode is a Hg / HgO electrode, the counter electrode is a carbon rod, and the electrolyte is a KOH solution; the size of the electrode sheet is 1~4 cm×1~4 cm.
8. An application of an organic-inorganic hybrid method to synthesize bifunctional fluorine-doped armor-type nanomaterials, characterized in that: The bifunctional fluorine-doped armor-type nanomaterial NiO according to any one of claims 1 to 6 1-x F x / Ni@C / NF is used as an electrocatalyst in an electrocatalytic urea oxidation device. In the electrocatalytic urea oxidation device, the working electrode is NiO 1-x F x / Ni@C / NF nanomaterial, the reference electrode is Hg / HgO electrode, the counter electrode is carbon rod, the electrolyte is KOH solution containing urea, and the electrolyte is 1 mol / L potassium hydroxide + 0.33 mol / L urea solution; The size of the electrode sheet is 1-4 cm×1-4 cm.
9. An application of an organic-inorganic hybrid method to synthesize bifunctional fluorine-doped armor-type nanomaterials, characterized in that: The bifunctional fluorine-doped armor-type nanomaterial NiO according to any one of claims 1 to 6 1-x F x / Ni@C / NF for electrocatalytic urea degradation.
10. The use of an organic-inorganic hybrid method for synthesizing bifunctional fluorine-doped armor-type nanomaterials according to claim 9, characterized in that: In the electrocatalytic urea degradation, both the anode electrode and the cathode electrode are NiO 1-x F x / Ni@C / NF nanomaterial, the electrolyte is 1 mol / L potassium hydroxide + 0.3 mol / L urea solution, and the size of the anode electrode sheet and the cathode electrode sheet are both 1~4 cm×1~4 cm.
Citation Information
Patent Citations
Preparation method of carbon-coated lithium iron phosphate material with carbon black as carbon source
CN103346315A
Preparation method of ferro-fluorine co-doped nickel phosphide and application of ferro-fluorine co-doped nickel phosphide in hydrazine oxidation assisted electrolysis of sea water to produce hydrogen
CN115161696A